Eyrbyggja saga and Legal Change - Valle, Julian E., 1988- (2017)
The discussion about saga origins and specifically about the temporal frame in which they were committed to parchment has been traditionally circumscribed to the literary field. Despite several attempts to enrich the debate considering the historical context (Torfi Tulinius, 2000, 2007, 2013), the scholarly consensus seems reluctant to redefine the datings traditionally accepted. Although a precise dating is a desideratum, a more concise framing for sagas could be useful to understand the context of their production. The saga genre is characterized by its connection with the upper ladders of Icelandic society and its nature as an historicizing discourse (Assman, 1992). Therefore, it is expected that there is an underlying political message, connected with the material circumstances of its production. This thesis considers Eyrbyggja saga as one of such cases. This saga has several advantages for an historical analysis. Firstly, it is a regional saga, most probably written in the area where the story takes place. Secondly, it has been linked with one of the most important families in the 13th century Icelandic history, the Sturlungar. Thirdly, the dating hypotheses provided by previous scholars, f. ex. Einar Ól. Sveinsson, relied on a cross-reading between Eyrbyggja and Grágás (or a previous non-preserved law code). This approach limited plausible interpretations that consider later legal compilations, as the one that is carried out in this thesis. Following this statement, the saga could be read as a sort of roman à clef, emphasizing the political content of the narrative.1 In this sense, two study cases will be identified among the several storylines in Eyrbyggja. The criterion will be to choose those scenes that present conflicting claims concerning the legal frame of the presumed period of its composition. From these cases, a comparative reading will be proposed between the saga and the legal corpora in force in Iceland since 1230 (the earliest proposed dating) to 1280 (the latest proposed dating). The ...